A study of cultural representation in Hokkien (Southern Min) textbooks - Huang, Yuannan; Song, Haoyan (Frontiers in Education, 2024)
This research employed a framework for analysing cultural representations within textbooks to focus on the three dimensions of geographical contexts, types of cultures and modes of presentation. A quantitative analysis of Hokkien textbooks from Fujian and Taiwan was conducted. The findings revealed that, on one hand, textbooks from both regions predominantly featured Minnan culture with a marked emphasis on cultural products related to the social life and traditional culture of China. On the other hand, the Fujian textbooks tended to present culture via knowledge blocks, whereas Taiwanese textbooks used cultural discourse for cultural presentations. This distinction emphasises the pivotal role of language education in perpetuating local cultures and values, as well as the challenges entailed in broadening the cultural scope. The outcomes of this study contribute to minimising the impact of regional factors in textbook research and provide empirical support for enhancing the quality of Hokkien education and the cultural adaptability of teaching materials.